LINGUOPRAGMATIC CHARACTERISTICS OF ALLEGORICAL MEANS (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Allegory is a stylistic trope that can make the artistic text and oral speech meaningful and convey the meaning to the listener and reader in a colorful way. Allegory is considered a type of movement and means revitalization. This article talks about the linguocognitive and linguopragmatic features of allegory and their peculiarities.